2003
DOI: 10.1183/09031936.03.00110202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bronchoalveolar cells in pulmonary paracoccidioidomycosis

Abstract: To investigate the local immune response, the cellular infiltrate and cytokine levels were analysed in bronchoalveolar lavage (BAL) from patients with pulmonary paracoccidioidomycosis. The group consisted of 19 patients aged 34-65 yrs. The diagnosis was confirmed by demonstration of the fungus in the sputum or BAL fluid and by serological tests.Cytospin preparations showed an increased number of lymphocytes and neutrophils in BAL. A higher number of CD8z lymphocytes were observed in BAL compared with periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…Several groups addressed this question by quantifying the cytokines released in vitro from patients' cells. The results published so far were, in general, quite concordant and the picture that emerged were quite consistent, as depicted in Table 2 [19,25,[27][28][29][30][31][32][33][34]. In brief, these studies showed that the acute/subacute form of the disease is associated with down modulation of the Th-1 cytokine pattern and expression of a dominant Th-2 immunity consisting of high levels of a subset of cytokines such as IL-4, IL-5 and IL-10, specific antibodies of the IgE and IgG4 subclasses, in situ and peripheral blood eosinophilia, among other parameters.…”
supporting
confidence: 61%
“…Several groups addressed this question by quantifying the cytokines released in vitro from patients' cells. The results published so far were, in general, quite concordant and the picture that emerged were quite consistent, as depicted in Table 2 [19,25,[27][28][29][30][31][32][33][34]. In brief, these studies showed that the acute/subacute form of the disease is associated with down modulation of the Th-1 cytokine pattern and expression of a dominant Th-2 immunity consisting of high levels of a subset of cytokines such as IL-4, IL-5 and IL-10, specific antibodies of the IgE and IgG4 subclasses, in situ and peripheral blood eosinophilia, among other parameters.…”
supporting
confidence: 61%
“…In this study, the alveolar macrophages over expressed ICAM-1, and other molecules on their surfaces, and they produced higher levels of IL-6, TNF-a and MIP-1a, indicating their participation in the pathogenesis of pulmonary PCM [91].…”
Section: Expression Of Adhesion Moleculesmentioning
confidence: 48%
“…In human studies, Fornazim et al [91], found increased number of lymphocytes and PMNs in BALs of patients with PCM. In this study, the alveolar macrophages over expressed ICAM-1, and other molecules on their surfaces, and they produced higher levels of IL-6, TNF-a and MIP-1a, indicating their participation in the pathogenesis of pulmonary PCM [91].…”
Section: Expression Of Adhesion Moleculesmentioning
confidence: 98%
“…Along the same lines, Fornazim et al [37], found increased number of lymphocytes and neutrophils in bronchoalveolar lavages of patients with PCM. The alveolar macrophages overexpressed ICAM-1, as well as other molecules (major histocompatibility class II and B7-2) on their surfaces and they produced higher levels of IL-6, TNF-a and MIP-1a, indicating that both were activate and participated in the pathogenesis of pulmonary PCM [37].…”
Section: Discussionmentioning
confidence: 72%